Large margin kernel methods for calmodulin binding prediction - Hamilton, Michael, author; Ben-Hur, Asa, advisor; Anderson, Charles, committee member; Iyer, Hariharan, committee member (Colorado State University. Libraries, 2010)
Protein-protein interactions are involved in nearly all molecular processes of organisms. However direct laboratory techniques for identifying binding partners remain expensive and difficult at the proteome scale. In this work, kernel methods for predicting calmodulin binding partners and calmodulin binding sites are presented. Furthermore, we compare binary and structural support vector machines with multiple kernels defined over protein sequences.
Covers not scanned.
Keywords: Kernel functions; Calmodulin; Calcium-binding proteins